The development of Seri Aman Caterer management system / Nurul Nabilah Khafidz - Khafidz, Nurul Nabilah (2017)
Seri Aman Caterer is a food business that focus on food catering for wedding, corporate events, private parties and hi-tea that located in Banting, Selangor. Currently, this food business is using manual method of booking where customer need to meet with the stakeholder for discussing about what catering service that customer want for their event. From the current process, the aim of this project is focusing on solving the problem that Seri Aman Caterer had where to develop a management system for Seri Aman Caterer. The problem that Seri Aman Caterer faces are no reference for their customer in order to booking Seri Aman Caterer service, last minute changes of the event menu and the last problem is late payment from their customer. From all the problems that Seri Aman Caterer had, the objectives are to gather and analyze the requirement, to design the system based on requirements and to develop the system based on the design for Seri Aman Caterer. In order to achieve the objectives, an interview session with the stakeholder have been made for gather the requirements. Other than that, the requirements and design is documented in Software Requirement Specification (SRS) and Software Design Document (SDD). From that, the system is develop by referring the SRS and SDD. During completing this project, the methodology that had being used is waterfall model where this type of methodology is suitable with short term project where the duration that being given in completing this project is just a year. In completing this project that have a few plan that have being documented for the project future work. The main future work is to make a testing with stakeholder. Where this testing will ensure that this project are truly based on needs and expectation.